Geospatial Mapping of Air Pollution and Health Risks in the Klang Valley: Insights for Industrial Sustainability - Patrick, Hanna Humaira; Misbari, Syarifuddin; Aziz, Norsaffarina; Sao, Vibol; Adman, Mohammad Adam (Popular Scientist, 2026)
Air pollution is a significant environmental issue that poses serious health risks, particularly in industrial areas. This study focuses on evaluating the spatial distribution of air pollutants and their impact on public health in the industrial areas of Shah Alam and Petaling Jaya in the Klang Valley, Malaysia. This study examines concentrations of particulate matter (PM10 and PM2.5), sulfur dioxide (SO2), nitrogen dioxide (NO2), ozone (O3), and carbon monoxide (CO) over a 2021, 2022, and 2023. Utilizing Geographic Information System (GIS) tools, the study maps the spatial distribution of the health risk in industrial are and correlates them with air pollutants data obtained from Department of Environmental, Malaysia (DOE). The trend of air quality in Shah Alam and Petaling Jaya reveals variation in pollutants concentrations, influenced by both natural and anthropogenic factors, with Shah Alam generally exhibiting higher level of SO2, NO2 and O3, while Petaling Jaya shows elevated CO levels. The differences between Shah Alam and Petaling Jaya’s air quality likely from varying meteorological factors, such as wind patterns, temperature, and humidity, which can influence the dispersion and concentration of pollutants. This underscores the critical need for targeted air quality management strategies to mitigate health risk associated with industrial pollution and urbanization in these regions.